A highly integrated dual-band triple-mode transmit IC for cellular CDMA2000 applications. - Aggarwal, S.
A highly integrated transmit integrated circuit intended for dual-band (CELL/PCS) and triple-mode (CDMA/TDMA/AMPS) cellular mobile stations is presented. It features a linear-in-dB gain-control range of 90 dB and provides a high output power of 9 dBm (PCS band) while meeting linearity requirements (-53-dBc ACPR) and achieving the receive-band noise floor of -133 dBm/Hz. It consumes only 130-mA current (3-V supply) in the PCS band. A dynamic-biasing feature results in additional power savings at lower signal levels. The circuit is fabricated in a 30-GHz fT BiCMOS technology.
Keywords: 130 mA; 3 V; 30 GHz; 30-GHz BiCMOS technology; PCS band; Analog mobile phone service; Cellular CDMA2000 applications; Dual-band cellular mobile stations; Dual-band radio; Dynamic-biasing feature; High output power; Highly integrated dual-band triple-mode transmit IC; Linear-in-dB gain-control range; Linearity requirements; Multimode radio; Power savings; Receive-band noise floor; Triple-mode cellular mobile stations